2011
DOI: 10.1111/j.1751-7133.2011.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Nurse Practitioner Disease Management Model for Chronic Heart Failure: A Multi‐Site Implementation Study

Abstract: While disease management appears to be effective in selected, small groups of CHF patients from randomized controlled trials, its effectiveness in a broader CHF patient population is not known. This prospective, quasi-experimental study compared patient outcomes under a nurse practitioner-led disease management model (intervention group) with outcomes under usual care (control group) in both primary and tertiary medical centers. The study included 969 veterans (458 intervention, 511 control) treated for CHF at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 30 publications
(59 reference statements)
1
58
0
Order By: Relevance
“…Asch et al however using this design was able to demonstrate the benefits of a collaborative organizational care intervention in CHF [12]. Other small but limited examples for CHF have also been published [12][13][14][15].…”
Section: Monitoring Patients Status and Response To Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Asch et al however using this design was able to demonstrate the benefits of a collaborative organizational care intervention in CHF [12]. Other small but limited examples for CHF have also been published [12][13][14][15].…”
Section: Monitoring Patients Status and Response To Treatmentmentioning
confidence: 98%
“…For cardiovascular disease as a whole, some large studies have been reported, mostly positive [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], although longer term translation of findings into actual clinical care within those systems is unknown.…”
Section: Monitoring Patients Status and Response To Treatmentmentioning
confidence: 99%
“…Estimated cost savings were explicitly reported in three studies (Williams, Assassa et al 2005, Allcock 2009, Allen, Dennison Himmelfarb et al 2014) where other studies reported decreased use of services which would ultimately result in cost savings for the health care system. Examples of this include decreased use of emergency departments (Newcomb 2006, Owens, Eby et al 2012, Murphy, Siebert et al 2013, Roots and MacDonald 2014, reduced hospital admissions (Newcomb 2006, Allcock 2009, Godleski, Cervone et al 2012, Lowery, Hopp et al 2012, Murphy, Siebert et al 2013, Roots and MacDonald 2014, decreased length of stays (Godleski, Cervone et al 2012) and reduced visits to a general practitioner (Newcomb 2006, Allcock 2009, Enguidanos, Gibbs et al 2012, Murfet, Allen et al 2013, Prasad, Dunn et al 2014. Although the majority of studies reporting on use of services found promising results, two studies reported statistically insignificant results related to changes in the use of hospital and general practitioner services (Tung, Kaufmann et al 2012, Sawatzky, Christie et al 2013).…”
Section: Societal Benefitsmentioning
confidence: 99%
“…Fourth, 65% of practicing nephrologists in 2010 were under the age of 55 years, suggesting that the current nephrology workforce has many years yet to practice (20). When assessing future demand, it will be essential to incorporate care models that fully incorporate nurse practitioners and physician assistants, which has happened in many other specialties (29,30). Pursuing this model in nephrology practices will align nicely with current trends toward more team-based care but likely further reduce demand for nephrologists.…”
Section: Right Sizing the Nephrology Workforcementioning
confidence: 99%